Find the derivative:
Problem 1 :
y =∜(7m³ - 4m² + 2)
Solution :
y = ∜(7m³ - 4m² + 2)
y = (7m³ - 4m² + 2)1/4, then g(m) = 7m³ - 4m² + 2
Let f(m) = m1/4
f’(m) = (1/4) m-3/4
f’(m) = 1/4m3/4
g(m) = 7m³ - 4m² + 2
g’(m) = 21m² - 8m
dy/dm = f’(g(m)) g’(m)
= [ 1/4(7m³ - 4m² + 2)3/4 ] · 21m² - 8m
dy/dm = (21m² - 8m) / 4 ∜ (7m³ - 4m² + 2)³
Problem 2 :
c = ∛ (4k² + 3)²
Solution :
c = ∛ (4k² + 3)²
c = (4k² + 3)2/3
Let f(k) = k2/3, then g(k) = 4k² + 3
f’(k) = (2/3) k-1/3
f’(k) = 2/3k1/3
g(k) = 4k² + 3
g’(k) = 8k
dc/dk = f’(g(k)) g’(k)
= [2/3(4k² + 3)1/3] · 8k
dc/dk = 16k / 3∛ (4k² + 3)
Problem 3 :
r = ∜ (4w + 3)5
Solution :
r = ∜ (4w + 3)5
r = (4w + 3)5/4
Let f(w) = w5/4, g(w) = 4w + 3
f’(w) = (5/4) w1/4
g(w) = 4w + 3
g’(w) = 4
dr/dw = f’(g(w)) g’(w)
= 5/4 (4w + 3)1/4 · 4
dr/dw = 5 ∜ (4w + 3)
Problem 4:
d = 3 / √x + 2
Solution:
d = 3 / √x + 2
d = 3 (x + 2)-1/2
dd/dx = 3(-1/2) (x + 2)-3/2 · d/dx(x + 2)
= -3/2 d/dx(x + 2) / (x + 2)3/2
= -3(1 + 0) / 2(x + 2)3/2
= -3/2(x + 2)3/2
dd/dx = -3/2√(x + 2)3
Problem 5 :
f = 2 / √4e + 5
Solution :
f = 2 / √4e + 5
f = 2 (4e + 5)-1/2
df/de = 2 (-1/2)(4e + 5)-1/2-1 · d/de (4e + 5)
= -4 d/de (e + 5) / (4e + 5)3/2
= -4/(4e + 5)3/2
df/de = -4/√(4e + 5)³
Problem 6 :
g(x) = 1/√1 - 2x
Solution :
g(x) = 1/√1 - 2x
g(x) = 1 (1 - 2x)-1/2
g’(x) = (-1/2)(1 - 2x)-3/2 · d/dx (1 - 2x)
= - (-2) / 2(1 - 2x)3/2
= 1/(1 - 2x)3/2
g’(x) = 1/√(1 - 2x)³
Problem 7 :
k(n) = 4/√n2 + 6
Solution :
k(n) = 4/√n2 + 6
k(n) = 4 (n² + 6)-1/2
k’(n) = 4(-1/2) (n² + 6)-3/2 d/dn (n² + 6)
= -2(2n + 0) / (n² + 6)3/2
k’(n) = -4n / √(n² + 6)³
Problem 8 :
p(r) = 12 / ∜ (7 - r)5
Solution :
p(r) = 12 / ∜ (7 - r)5
p(r) = 12 (7 - r)-5/4
p’(r) = 12(-5/4) (7 - r)-9/4 d/dr (7 - r)
= -15(0 - 1) / (7 - r)9/4
p’(r) = 15 / ∜ (7 - r)9
Problem 9 :
q(z) = 5 / 5√ (z5 - 32)
Solution :
q(z) = 5 / 5√ (z5 - 32)
q(z) = 5 (z5 - 32)-1/5
q’(z) = 5 (-1/5) (z5 - 32)-6/5 d/dz (z5 - 32)
= - (5z4 - 0) / (z5 - 32)6/5
q’(z) = -5z4 / 5√ (z5 - 32)6
May 21, 24 08:51 PM
May 21, 24 08:51 AM
May 20, 24 10:45 PM